2022
DOI: 10.3389/fmicb.2022.943097
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of egg component and its association with hatchability of laying hens

Abstract: The internal quality of eggs is critical for human consumption and embryonic development. However, microorganisms inside eggs have not been thoroughly investigated for their roles in determining the egg’s internal quality. Here, a total of 21 hens were selected from more than 1,000 chickens based on their hatching results and were divided into high- and low-hatchability groups. Then, we collected 72 eggs from these 21 hens to obtain egg whites and yolks, including 54 fresh eggs and 18 eggs after 12 days of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Similar studies were also done by Jin ey al. [25] that eggs have diverse microbial compositions which have a direct impact on their hatchability. Eggs are nutritious, but contamination by coliform bacteria and other dangerous organisms also causes major health issues.…”
Section: Discussionmentioning
confidence: 99%

Molecular diagnosis of hen eggs microbiota

Ahmed M. Al-Hejin,
Mohamed Morsi M. Ahmed,
Sana Ghazi Alattasa
et al. 2024
Cell Mol Biol (Noisy-le-grand)
“…Similar studies were also done by Jin ey al. [25] that eggs have diverse microbial compositions which have a direct impact on their hatchability. Eggs are nutritious, but contamination by coliform bacteria and other dangerous organisms also causes major health issues.…”
Section: Discussionmentioning
confidence: 99%

Molecular diagnosis of hen eggs microbiota

Ahmed M. Al-Hejin,
Mohamed Morsi M. Ahmed,
Sana Ghazi Alattasa
et al. 2024
Cell Mol Biol (Noisy-le-grand)
“…The results showed that the bacteria on eggshells changed as a function of the area [8] and the breed of the chicken [10], as well as due to farming practices, including the cages [10], food, and water used [3]. The microbiota in egg contents were tightly associated with the storage time [11]. However, information about the impacts of the different seasons on the microbiota on eggshells remains scarce, and these impacts involve changes in temperature, humidity, rainfall, light, etc.…”
Section: Introductionmentioning
confidence: 99%